2018
DOI: 10.3389/fneur.2018.00704
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral White Matter Changes in Young Healthy Individuals With High Trait Anxiety: A Tract-Based Spatial Statistics Study

Abstract: Background: Abnormalities in prespecified and empirical white matter tracts in young patients with anxiety-related disorders have been reported in some diffusion tensor imaging (DTI) studies. However, with few literatures examining the association between the integrity of whole brain white matter and trait anxiety levels in the non-clinical populations, whether white matter changes arise in young healthy individuals with high trait anxiety remains unknown.Methods: We examined whole brain white matter alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 69 publications
1
22
0
Order By: Relevance
“…To our knowledge, the investigation on white matter structural connectivity in young healthy people with high trait anxiety is limited. Our group previously used tract-based spatial statistics method to detect the changes of white matter in young healthy populations with high trait anxiety (8). In this study, our results showed widespread abnormal connections in brain regions, but no significant difference in the network property was detected.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…To our knowledge, the investigation on white matter structural connectivity in young healthy people with high trait anxiety is limited. Our group previously used tract-based spatial statistics method to detect the changes of white matter in young healthy populations with high trait anxiety (8). In this study, our results showed widespread abnormal connections in brain regions, but no significant difference in the network property was detected.…”
Section: Discussionmentioning
confidence: 54%
“…For the non-clinical population with high trait anxiety level, few neuroimaging studies have focused on brain connectivity. Our previous study used tract-based spatial statistics method to compare white matter differences among young healthy individuals with low and high trait anxiety levels (8). Alterations in the thalamus-cortical circuit and some emotion-related areas are commonly reported in anxiety-related disorders (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been found that there is a high prevalence of clinical anxiety in people living with HIV (Janssen et al 2015; Brandt et al 2017), and that anxiety is associated with poorer performance on cognitive tests (Laverick et al 2017), similar to findings of increased anxiety in mild cognitive impairment (MCI) (Chen et al 2018). It has also been noted that there may be white matter abnormalities on DTI in people with anxiety-related disorders in the absence of HIV (Lochner et al 2012; Lu et al 2018). Taken together, these findings suggest that there may be a role for screening and treating anxiety and depression in patients with HAND (Seedat 2012; Spies et al 2013; Wu and Li 2013; Sacktor et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, the alteration of white matter microstructure involved in anxiety-related personality traits is not restricted to corticolimbic pathways. For example, harm avoidance in adult subjects was positively associated with radial and mean diffusivity, not only in the uncinate fasciculus but also in the anterior thalamic radiation, corpus callosum, parahippocampal cingulum, corticospinal tract, and inferior and superior longitudinal fasciculi (Westlye et al, 2011;Lu et al, 2018). Reduced FA was also detected in the medial and posterior portions of the corpus callosum of children with post-traumatic stress disorder (PTSD; Jackowski et al, 2008), and altered inter-hemispheric frontal, frontal-limbic, or frontal-temporal connectivity was identified as a potential marker of vulnerability to anxiety in young healthy subjects (Yang et al, 2019) and symptomatic anxiety in patients with late-life depression (Li et al, 2020).…”
Section: Myelin and White Matter Alterations In Stress-and Anxiety-rementioning
confidence: 99%